2018
DOI: 10.11604/pamj.2018.30.30.14835
|View full text |Cite
|
Sign up to set email alerts
|

Acute urinary retention due to benign prostatic hyperplasia associated with cystitis glandularis in a 22-year-old patient

Abstract: A 22-year-old man has consulted in emergency for acute urinary retention and left renal colic. Bladder catheterization was performed. Symptomatic treatment was provided with no improvement. MRI showed a pseudotumoral bladder wall thickening associated with vesical floor budding with prostate median lobe infiltration. The patient got an endoscopy that concluded to an inflammatory aspect of the bladder mycosa and a solid mass in the bladder neck arising. The biopsy during examination concluded to a glandular cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…And these symptoms are prone to recurring. In severe cases, acute urinary retention mayoccur ( 7 ). For the treatment of glandular cystitis, some people advocate conservative treatment such as the use of quinolone antibiotics and cyclooxygenase-2 inhibitors ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…And these symptoms are prone to recurring. In severe cases, acute urinary retention mayoccur ( 7 ). For the treatment of glandular cystitis, some people advocate conservative treatment such as the use of quinolone antibiotics and cyclooxygenase-2 inhibitors ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Direkomendasikan menggunakan terapi Alpha blockers dan/ atau 5-alpha reductase inhibitors (Alfuzosin 10 mg PO dan dutasteride 0,5 mg PO). Dalam kasus kegagalan perawatan medis, atau komplikasi seperti retensi urin akut, ISSN 2301-5977, e-ISSN 2527-7154 https://journal.unram.ac.id/index.php/LJU/index infeksi saluran kemih, atau lithiasis kandung kemih, operasi endoskopi atau prostatektomi terbuka dapat dilakukan tergantung pada volume prostat (Zouari et al, 2018). Pemberian kombinasi alfuzosin dan dutasteride karena dapat memberikan efek sinergis antara manfaat kedua obat, sehingga dapat menghasilkan terapi yang lebih baik.…”
Section: Hasil Dan Pembahasanunclassified
“…Zouari et al [44] reported a 22-year-old man, who did not have any past medical history, who had consulted in emergency for acute urinary retention and left renal colic. Bladder catheterization was undertaken as well as an ultrasound scan which showed left obstructive pre-meatus calculi of 6 mm and distension of his urinary bladder.…”
mentioning
confidence: 99%
“…Upon examination the patient was found to be afebrile and a slight tenderness on the left flank was found upon his abdominal palpation. Upon digital examination (DRE), Zouari et al [44] found an enlarged prostate gland; there were no indurations and no areas of softness or tenderness within the prostate gland found during the examination. An anti-inflammatory and antalgic treatment was provided to the patient.…”
mentioning
confidence: 99%
See 1 more Smart Citation